APOBEC-related mutagenesis and neo-peptide hydrophobicity: implications for response to immunotherapy. (4th March 2019) - Boichard, Amélie; Pham, Timothy V.; Yeerna, Huwate; Goodman, Aaron; Tamayo, Pablo; Lippman, Scott; Frampton, Garrett M.; Tsigelny, Igor F.; Kurzrock, Razelle
ABSTRACT: Tumor-associated neo-antigens are mutated peptides that allow the immune system to recognize the affected cell as foreign. Cells carrying excessive mutation load often develop mechanisms of tolerance. PD-L1/PD-1 checkpoint immunotherapy is a highly promising approach to overcome these protective signals and induce tumor shrinkage. Yet, the nature of the neo-antigens driving those beneficial responses remains unclear. Here, we show that APOBEC-related mutagenesis – a mechanism at the crossroads between anti-viral immunity and endogenous nucleic acid editing – increases neo-peptide hydrophobicity (a feature of immunogenicity), as demonstrated by in silico computation and in the TCGA pan-cancer cohort, where APOBEC-related mutagenesis was also strongly associated with immune marker expression. Moreover, APOBEC-related mutagenesis correlated with immunotherapy response in a cohort of 99 patients with diverse cancers, and this correlation was independent of the tumor mutation burden (TMB). Combining APOBEC-related mutagenesis estimate and TMB resulted in greater predictive ability than either parameter alone. Based on these results, further investigation of APOBEC-related mutagenesis as a marker of response to anti-cancer checkpoint blockade is warranted.